2013
DOI: 10.1159/000348881
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ovarian Surface Epithelium in Folliculogenesis during Fetal Development of the Bovine Ovary: A Histological and Immunohistochemical Study

Abstract: Although many aspects of ovarian differentiation have been established, comparatively little is known about prenatal follicle formation and differentiation of bovine ovaries. The objective of this investigation was to study the role of the surface epithelium during the development of germ cell nests, germ cell cords and follicle formation in the fetal bovine ovary. Associated important proliferation and apoptotic features were further investigated. Additionally, the expression pattern of the S100 protein was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 57 publications
8
40
0
9
Order By: Relevance
“…7A). In support of this, both Garverick et al (2010) and Kenngott et al (2013) noted the lack of a well-formed epithelium in developing ovarian tissues in cattle, while McNatty et al (2000) also reported a less-prominent epithelial layer following initial formation of the gonadal ridge. Further evidence supporting the lack of a mature ovarian surface epithelium comes from the observation that surface epithelial expression of ESR1, a characteristic of the ovarian surface epithelial layer is not noted until at least day 55 in sheep and day 75 in cattle (Garverick et al 2010).…”
Section: Ovigerous Cord Formationmentioning
confidence: 68%
See 1 more Smart Citation
“…7A). In support of this, both Garverick et al (2010) and Kenngott et al (2013) noted the lack of a well-formed epithelium in developing ovarian tissues in cattle, while McNatty et al (2000) also reported a less-prominent epithelial layer following initial formation of the gonadal ridge. Further evidence supporting the lack of a mature ovarian surface epithelium comes from the observation that surface epithelial expression of ESR1, a characteristic of the ovarian surface epithelial layer is not noted until at least day 55 in sheep and day 75 in cattle (Garverick et al 2010).…”
Section: Ovigerous Cord Formationmentioning
confidence: 68%
“…However, these migrating cells are exclusively endothelial cells, which form the testis-specific vasculature (Jeays-Ward et al 2003, Combes et al 2009). In contrast in sheep, mesenchymal cells of the giant nephron are thought to migrate into the ovary before sexual differentiation (Zamboni et al 1979), a phenomenon also observed in cattle (Kenngott et al 2013). In addition, in cattle the presence of mesonephric-tissue-derived GREL cells also appears to precede sexual differentiation.…”
Section: Migration Of Mesonephric Cellsmentioning
confidence: 95%
“…A diminuição gradativa dos cordões ovígeros parece ser uma caracterís-tica conservada ao longo do processo evolutivo e tem sido relatada em outras espécies de mamíferos, como por exemplo, em macacas (Fouquet & Dang 1980), ovelhas (Sawyer et al 2002), bovinos (Kenngott et al 2013) e seres humanos (Konishi et al 1986), bem como na espécie de codorna Coturnix coturnix japonica (Madekurozwa 2012).…”
Section: Discussionunclassified
“…The protocol of granulosa cell proliferation by using Ki-67 immunostaining was adapted from a previous study [23]. After histological tissue preparation, sections were treated for antigen retrieval in an autoclave machine (121°C, 1.2 kg/cm 2 ) for 30 min in citrate buffer (pH = 6.0).…”
Section: Proliferation Assessmentmentioning
confidence: 99%